PENGEMBANGAN MODEL BISNIS AGROINDUSTRI GULA KELAPA KRISTAL BERIODIUM - Dian Novitasari; Hety Handayani Hidayat (Jurnal Teknologi Industri Pertanian, 2021)
This study aims to describe the current condition of the iodized crystal coconut sugar agro-industry business model and to determine the appropriate canvas business model design for the agro-industry to be applied in its business development strategy. The data processing method uses a qualitative approach using SWOT analysis in combining the nine elements of the canvas business model. The results showed that the business model in the iodized crystal coconut sugar agroindustry is currently still being carried out in the old way by maintaining the same market segmentation, with limited marketing, so that it has not been able to maximize its business properly to get a profit so it is necessary to modify the business model. by narrowing its target market, developing production and marketing of its products. Keywords: BMC, crystal coconut sugar, iodized coconut sugar